First complete coding sequence of a Venezuelan Equine Encephalitis Virus Strain Isolated from an Equine Encephalitis case in Costa Rica - León, Bernal (2019)
This work was supported by Servicio Nacional de Salud Animal (SENASA), the Ministerio de Agricultura y Ganadería (MAG), Universidad Nacional (UNA), and the Ministerio de Planificación through OPES-60-2017-d-Consejo Nacional de Reactores (CONARE)-Costa Rica funding.